Early-onset neonatal sepsis in a 32- week old preterm newborn caused by non-typable Haemophilus influenzae: Early-onset neonatal sepsis in a 32- week old preterm newborn caused by non-typable Haemophilus influenzae: clinical case study (Archives of Pediatrics of Uruguay, 2025)
Early neonatal sepsis is an important cause of neonatal morbidity and mortality. Its incidence is inversely proportional to gestational age.Haemophilus influenzae is a pleomorphic gram-negative coccobacillus, present in the upper respiratory tract of humans, its mode of transmission is interpersonal, by inhalation of flugge droplets or direct contact with respiratory secretions. In the case of newborns, the infection can be acquired intra-uterus, during childbirth by aspiration of amniotic fluid or by contact through vaginal secretions that contain the microorganism.The serotype most frequently involved is the non-typeable one, responsible for asymptomatic infections.We present the clinical case of a 32-week preterm newborn who developed difficult-to-manage refractory septic shock caused by non-typeable Haemophilus influenzae, which led to death in a few hours.
Keywords: Haemophilus Influenzae; Haemophilus Infections; Neonatal Sepsis